Experimental investigation of energy consumption and model identification of reverse osmosis desalination system fed by hybrid renewable energy source under different operating conditions. Issue 9 (13th June 2019) - Hossam‐Eldin, Ahmed; Abed, Kamal; Youssef, Karim; Kotb, Hossam
Abstract: In this article, the specific energy consumption (SEC) and water production cost ( C w ) of a reverse osmosis (RO) desalination plant are investigated experimentally under different working conditions. The plant is fed by a hybrid renewable energy source. The frequency of the high‐pressure pump motor is changed from 35 to 50 Hz using a variable frequency drive. In addition, the feed water temperature and the reject control valve are controlled. This article investigates the effects of SEC, C w, permeate salt concentration, and plant productivity. The results show that both SEC and C w are reduced by increasing the frequency up to 45 Hz before rising thereafter. Also, SEC and C w decrease with increasing feed temperature and reduced reject valve opening. As a result, the optimum values of SEC and C w are found at 45 Hz and 40 °C with 25% valve opening, representing 4.5 kWh/m 3 and 0.55 /m 3, respectively. Then, a model is proposed for the RO plant using the Matlab identification toolbox. The model is validated by comparing the simulation results with the experimental data. Based on the best fit ratio, the model presents good results for verification, which can be used for a process control design. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.